Addictive States of Mind. - Bower, Marion (Karnac Books, 2013)
'Perversion is taken to mean different things within psychoanalytic discourse. In this book the authors view perversions, not in terms of specific behaviours, but as a type of blueprint for object relations. While perversions may involve a quest for excitement through sex, drugs or gambling, for example, the focus here is on the underlying incapacity - or indeed at times refusal - to relate to the other as separate from the self and not as a narcissistic appendage. It is the anxieties aroused by intimacy and relatedness that drive the pursuit of ecstasy and excitement. Psychoanalytic thinking.